Differences with Problem based Learning Models, Project based Learning Models And Interest in Learning Material Junior High 36 Football Terrain - Ariansyah Panggabean; Agung, Agung Sunarno; Ardi, Ardi Nusri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The purpose of this study is to analyze the difference between problem-based learning models, project-based learning models, and learning interests in football dribbling learning outcomes. The research method is experimental. The design of this study is an experimental design with a level of 2 x 2. Data collection techniques use observation, questionnaires and documentation. The number of research samples was 40 people with each group totaling 10 people. The data analysis techniques used were normality test, homogeneity test, anova test and tukey test. Based on the results of the research, Fh > Ft was obtained which was 4.17 > 4.06. So the overall conclusion can be drawn that there is an influence of dribbling learning outcomes in football games between problem-based learning and project-based learning. 2) Fh > Ft obtained is 78.37 > 4.06. Therefore, it can be concluded that there is an interaction between the learning model and learning interest on the learning outcomes of dribbling 3) It is obtained that Qh = 20.47 and Qt = 2.81 can be concluded that students taught with problem-based learning with high student learning interest are better than students taught with project-based learning with high student learning interest. 4) Qh = 13.65 and Qt = 2.81 were obtained and based on these results, it can be concluded that students taught with project-based learning with low student learning interest are better than students taught with problem-based learning with low student learning interest.